Does Recruitment Develop a Corporate Image to Attract Talented Candidates for Hiring in Bangladesh? - Afroze, Rumana (Asian Business Review, 2016)
Recruitment is one of the major functions of Human Resource Management (HRM) which is the process of attracting qualified candidates. Recruitment depends on some factors like recruitment cost, budget and sources of recruitment, etc. This study finds out how job advertisement and other recruitment methods develop corporate image and then it reveals how developed corporate image influence, talented candidates, to apply for the job. This study is a predominantly qualitative nature and presents study findings through the in-depth interview methods. Purposive sampling has used for selecting respondents. Respondents are potential candidates like fresh graduates, final year students, new employees as well as expert HR personnel. The study found that most of the candidates prefer multinational companies as well as reputed local organization to join because of their positive images. Respondents believe that employees of these companies are getting more facilities, more advancement and higher pay and benefits. Moreover, talent candidates also get information about the company from different job advertisement. Organization tries to create an attractive job advertisement by mentioning some information like salary structure, facilities, benefits, working environment and so on. This information mainly influences the candidate’s intention for applying in the organizations. In addition to this, new organizations often prefer to participate in the job fair and different career seminar for creating a positive company image. Their target is to influence the talent candidates for applying in their organization.